Evolocumab for the treatment of homozygous familial hypercholesterolaemia. (2nd July 2016) - Blom, Dirk Jacobus; Marais, A. David
ABSTRACT: Introduction : Homozygous familial hypercholesterolaemia (HoFH) is a genetic disorder of lipoprotein metabolism characterized by minimal or absent LDL-receptor (LDLR) function, markedly elevated low density lipoprotein cholesterol (LDLC) and premature atherosclerotic cardiovascular disease. Pharmacological control of LDLC in patients with HoFH is challenging. Areas covered : Evolocumab is a fully human monoclonal antibody directed against proprotein convertase subtilisin kexin type 9 (PCSK9). PCSK9 is a serine protease predominantly secreted by hepatocytes and interferes with physiological LDLR recycling. In HoFH monthly subcutaneous evolocumab 420mg lowers LDLC by 16-23% and by 41% from baseline compared to placebo in patients with at least one LDLR allele with residual function. Individual responses to evolocumab are highly variable. Increasing the dosing frequency to once every two weeks lowers LDLC by a further 6%. Evolocumab is not effective when both LDLR alleles carry mutations without residual function. Additionally, evolocumab lowers Lp (a) by approximately 10% in patients with HoFH. Expert opinion : Evolocumab is an effective additional option for treating HoFH patients with residual LDLR function and is likely to be used routinely in the majority of patients in addition to statins and ezetimibe because of its good tolerability and safety. Many patients receiving the triple combination of a statin + evolocumab + ezetimibe will still require additional therapies such as lipoprotein apheresis, lomitapide or mipomersen to reach their LDLC target.